(untitled) - Gupta, Bhisham C. (Hoboken, New Jersey, 2013)
An understanding of statistical tools is essential for engineers and scientists who often need to deal with data analysis over the course of their work. Statistics and Probability with Applications for Engineers and Scientists walks readers through a wide range of popular statistical techniques, explaining step-by-step how to generate, analyze, and interpret data for diverse applications in engineering and the natural sciences.
Keywords: Probabilities,Mathematical statistics,Xác suất,Toán học thống kê